2022
DOI: 10.3389/fnut.2022.843938
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coronavirus Disease-19 Pandemic Lockdown and the Overlapping Ramadan Fasting Period on Glucose Control in Insulin-Treated Patients With Diabetes: A Flash Glucose Monitoring Study

Abstract: BackgroundA strict lockdown was enforced during coronavirus disease (COVID-19) pandemic in many countries including the UAE. Lockdown period overlapped with Ramadan which is accompanied by its own drastic changes in lifestyle that include meal timings.AimsWe report the impact of COVID-19 lockdown (between 22/3/2020 and 24/6/2020) on glucose control pre- and postlockdown and during Ramadan, in patients with type 1 diabetes (T1D) and type 2 diabetes (T2D) on insulin therapy.MethodsA number of twenty-four patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, previous studies have demonstrated an association of weekends and the Chinese New Year public holiday with increased in-hospital mortality in China (18,19). In addition, there is evidence that Ramadan fasting or COVID-19 lockdown characterized by changes in lifestyle that include sudden changes in mealtimes, sleep, and routine daily activity may affect the glycemic control in T1DM patients from a positive or negative standpoint (20)(21)(22)(23). Therefore, strengthening diabetes health education is especially important during the Chinese New Year public holiday to avoid acute and life threating complications, such as ketoacidosis and hyperosmolar coma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have demonstrated an association of weekends and the Chinese New Year public holiday with increased in-hospital mortality in China (18,19). In addition, there is evidence that Ramadan fasting or COVID-19 lockdown characterized by changes in lifestyle that include sudden changes in mealtimes, sleep, and routine daily activity may affect the glycemic control in T1DM patients from a positive or negative standpoint (20)(21)(22)(23). Therefore, strengthening diabetes health education is especially important during the Chinese New Year public holiday to avoid acute and life threating complications, such as ketoacidosis and hyperosmolar coma.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four patients (19 men, 6 women) who monitored their glucose levels using FGM and remotely connected to a diabetes clinic in UAE were included. 36 CGM metrics were calculated for each period: 30 days before lockdown, 30 days into lockdown and pre-Ramadan, and 30 days into lockdown and Ramadan. MAG remained steady before and during the lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have compared glycemic control for type 1 diabetes (T1D) and type 2 diabetes (T2D) before and after lockdown, and reported heterogeneous results [6,[17][18][19][20][21][22][23][24][25]. Some reports suggest that the use of advanced treatment (isCGM: intermittently scanned continuous glucose monitoring, CGM: continuous glucose monitoring, and SAP: sensor-augmented pump) may help maintain good glycemic control during the COVID-19 lockdown [6,18,24,25].…”
mentioning
confidence: 99%